Anxiety Level in Face-to-Face Communication by Age and Type of Occupation During Omicron Variant Transmission in Petanglong Central Java - Endro Tri Susdarwono (JURNAL LITBANG KOTA PEKALONGAN, 2022)
This study aims to examine anxiety level in face-to-face communication by age and type of occupation during Omicron variant transmission. The approach used in the research is quantitative. Data collection techniques using questionnaires were carried out in the Pekalongan City, Pekalongan Regency, and Batang Regency areas. The technique for analyzing data applied hypothesis testing using the contingency correlation method. This analysis tool through the contingency table is applied to determine the relationship between variables from data that includes qualitative aspects, including opinions, perceptions, or judgments about the characteristics of a situation. The transmission of the Omicron COVID-19 variant has a correlation with the level of anxiety in conducting face-to-face communication both according to age and job type criteria. Based on the criteria that apply to the research methodology, the correlation value in hypothesis testing according to age criteria is 45.53% and in hypothesis testing according to job type criteria, 45.42% is classified as moderate or sufficient. This research show that there is indeed a level of anxiety in the community in conducting face-to-face communication.  Keywords: face-to-face communication, Petanglong, anxiety level, omicron variant